Risk factors for repetition and suicide following self-harm in older adults: multicentre cohort study. - Murphy, E; Kapur, N; Webb, R; Purandare, N; Hawton, K; Bergen, H; Waters, K; Cooper, J (2012)
BACKGROUND: Older adults have elevated suicide rates. Self-harm is the most important risk factor for suicide. There are few population-based studies of self-harm in older adults. AIMS: To calculate self-harm rates, risk factors for repetition and rates of suicide following self-harm in adults aged 60 years and over. METHOD: We studied a prospective, population-based self-harm cohort presenting to six general hospitals in three cities in England during 2000 to 2007. RESULTS: In total 1177 older adults presented with self-harm and 12.8% repeated self-harm within 12 months. Independent risk factors for repetition were previous self-harm, previous psychiatric treatment and age 60-74 years. Following self-harm, 1.5% died by suicide within 12 months. The risk of suicide was 67 times that of older adults in the general population. Men aged 75 years and above had the highest suicide rates. CONCLUSIONS: Older adults presenting to hospital with self-harm are a high-risk group for subsequent suicide, particularly older men.